Portfolio Capital Flows: Not an unmitigated blessing. A literature survey (2019)
This paper is a literature survey on capital flows to developing countries. It analyzes the characteristics of the different components of capital flows. It also focuses on the factors, internal and external, that make capital flow into developing countries, as well as on the consequences of these flows -and their reversals- on the health of the recipient economies. Finally, it surveys the policies that have been implemented to handle them in search for the most recommendable ones. Its main conclusion is that capital inflows play a very important role for developing countries by being an alternative for these economies to undergo a path of growth, a possibility that otherwise will be undermined by the lack of sufficient domestic savings. However, there is a large number of risks associated with capital inflows which are magnified by the fact that capital-importing countries usually do not have neither adequate institutions, deep financial markets, strong banking systems, nor enough macroeconomic expertise. All these factors put together make capital inflows to developing countries “notan unmitigated blessing”